E0592 Study on the correlation between genetic polymorphism of angiotensin-converting enzyme (ACE) in Hainan Li Nationality and hypertension with atherosclerosis. (17th November 2010) - Meiling, Yun; Yin, Zheng; Janghua, Zhong; Yu, Zeng; Tianfa, Li; Yong, Zhang
Abstract : Objective: To study the correlation between genetic polymorphism of angiotensin-converting enzyme (ACE) in Hainan Li Nationality and hypertension with atherosclerosis. Methods: ACE I/D gene polymorphisms were detected by PCR in 260 hypertension with atherosclerosis group and 276 healthy groups from Hainan Li nationality, and investigated the genotype frequencies and allele frequencies of DD, DI and II. Results: (1) In the hypertension with atherosclerosis group of Hainan Li nationality, the genotype frequencies of DD, DI and II were 15.0%, 27.3%, 47.7% respectively, and the allele frequencies of D and I were 33.7% and 66.3% respectively. In the healthy control of Hainan Li nationality, the genotype frequencies of DD, DI and II were 17.8%, 40.6% and 41.7% respectively, and the allele frequencies of D and I were 38.0% and 62.0% respectively. There were no significant differences both in the genotype frequencies of DD, DI and II, and in allele frequencies D and I between these two groups (p>0.05). (2) The logistic regression showed that there were associations between TG (OR=2.14), ApoA (OR=360.39), SBP (OR=1.21), DBP (OR=1.08) and the hypertension with atherosclerosis group (p<0.05). The MIMT level in ACE DD subset were significant higher than in DI and II (p<0.05). Conclusions: The ACE DD genotype increases the susceptibility of carotid atherosclerosis. It is the risk factor in the hypertension with atherosclerosis group of Hainan Li nationality. It may be an early prediction factor in atherosclerosis.